ECONOMIC PRINCIPLES OF MILK PRODUCTION IN AGRICULTURE OF VINNITSA REGION - MAZUR, KATERYNA; HONTARUK, JAROSLAW (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The analysis of milk market development in modern conditions is carried out. The article examines the indicators of raw materials at enterprises of processing industries by quality indicators of dairy products. The article considers the theoretical and methodological principles and problems of organizational and economic nature of the dairy industry. Emphasis is placed on the content, structure and problems of functioning of the dairy complex, substantiation of the organizational and economic mechanism of ensuring the production of competitive products in the industry. It is determined that the achievement of competitiveness of products and enterprises of the dairy subcomplex requires close cooperation, mutually beneficial partnership of all its structural units. It is determined that the location of milk production is a factor influencing the improvement of the organization of the industry in agricultural enterprises of Vinnytsia region. Areas (groups of districts) that specialize in milk production have been identified, which indirectly indicates the lack of targeted regional policy to influence the improvement of the location of the industry. is a sign of low level of development of dairy cattle breeding of the region. The almost predominant dominant role of households in the regional milk market has been identified. The situation will not change significantly in the coming years, and the current trend will continue. The proposed way out of this situation is the creation of dairy farms with the participation of large dairy plants in order to provide the latter with high quality raw materials. Prospects for the establishment of subsidiaries of dairy plants - the creation of agricultural enterprises in the dairy direction.
Keywords: milk processing enterprises; milk; dairy industry; market; restructuring; mechanism; strategy; raw materials